Playing catch-up with Escherichia coli: using yeast to increase success rates in recombinant protein production experiments - Bill, Roslyn M. (Frontiers in Microbiology, 2014)
Several host systems are available for the production of recombinant proteins, ranging from Escherichia coli to mammalian cell-lines. This article highlights the benefits of using yeast, especially for more challenging targets such as membrane proteins. On account of the wide range of molecular, genetic and microbiological tools available, use of the well-studied model organism, Saccharomyces cerevisiae, provides many opportunities to optimize the functional yields of a target protein. Despite this wealth of resources, it is surprisingly under-used. In contrast, Pichia pastoris, a relative new-comer as a host organism, is already becoming a popular choice, particularly because of the ease with which high biomass (and hence recombinant protein) yields can be achieved. In the last few years, advances have been made in understanding how a yeast cell responds to the stress of producing a recombinant protein and how this information can be used to identify improved host strains in order to increase functional yields. Given these advantages, and their industrial importance in the production of biopharmaceuticals, I argue that S. cerevisiae and P. pastoris should be considered at an early stage in any serious strategy to produce proteins